Food Safety, Market Organization, Trade and Development 2015
DOI: 10.1007/978-3-319-15227-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Standards and International Trade: The Impact on Developing Countries’ Export Performance

Abstract: The expansion of food safety standards in regulations has introduced new complexity in trade policy dialogues and efforts to expand trade in agricultural products. A loss of competitiveness due to the costs required to comply with these standards has arisen concern among exporting firms, particularly those in developing countries. This chapter reviews and synthesizes existing studies that quantify the impact of food safety standards with particular attention to developing countries' access to international mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Partners (as well as Pakistan) should attain valuable and useful lessons to advance their technical standards by initiating the measure(s), and processing them before exporting the merchandise to the demanding economies. This result further supports the idea of Devadason and Govindaraju (2016), Keiichiro, et al (2015), Kapuya (2015), Otsuki, et al (2000), Moenius (2004), Da Silva-Glasgow, and Hosein (2018), among others. Similarly, high and lower middle income countries show similar patterns of coefficients, but the remaining two groups, i.e., upper and lower income countries, show opposite signs.…”
Section: Estimation Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Partners (as well as Pakistan) should attain valuable and useful lessons to advance their technical standards by initiating the measure(s), and processing them before exporting the merchandise to the demanding economies. This result further supports the idea of Devadason and Govindaraju (2016), Keiichiro, et al (2015), Kapuya (2015), Otsuki, et al (2000), Moenius (2004), Da Silva-Glasgow, and Hosein (2018), among others. Similarly, high and lower middle income countries show similar patterns of coefficients, but the remaining two groups, i.e., upper and lower income countries, show opposite signs.…”
Section: Estimation Results and Discussionsupporting
confidence: 89%
“…In spite of all this, the developing countries are affected the worse because of compliance hitches. Several other studies found a negative relation between import and TBT under WTO regime including Devadason and Govindaraju (2016), Keiichiro, et al, 2015), Da Silva-Glasgow andHosein (2018), andSanjuan, et al (2017). TBT has trade distorting impacts, found by Kapuya (2015), Otsuki, et al (2000), and Moenius (2004).…”
Section: Empirical Literature On Technical Barriers To Tradementioning
confidence: 88%
“…This proves that although TBT improves the products quality but it also restricts import of commodities. Similar results supports the ideas of Otsuki et al (2000), Kapuya (2015), Keiichiro et al (2015), Devadason and Govindaraju (2016), Da Silva-Glasgow andHosein (2018), andMoenius (2004).…”
Section: The Impact Of Sanitary and Phytosanitary Measures And Techni...supporting
confidence: 92%
“…The question associated with food safety is largely dominated by the concern linked to food security in terms of quantitative acceptance (Henson and Jaffee, 2007;Henson and Blandon, 2007). Consequently, food production in many DCs often has limited standardisation and minimal imposition of food safety requirements, except in export sectors where constraints are set by importing countries (Keiichiro et al, 2015)[5]. However, consumers in DCs are increasingly exposed to high levels of various risks with the food they consume such as pesticides (WHO, 2004) or food poisoning (toxins and E-coli) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Food safety regulations 5. Not that the majority of available works addressing food safety issues in DCs adopt an international trade perspective (Keiichiro et al, 2015). Economists do not neglect the consumer health issue, but the predominance of strategic development plans based on exports have, to a certain extent, oriented the economic literature in this direction, by relaying the DCs' donors' and public authorities' concerns (Unnevehr, 2015).…”
mentioning
confidence: 99%